Vicky Hayward: New Art of Cookery, a Spanish friar’s kitchen notebook by Juan Altamiras & Vicky Hayward: Nuevo Arte de la Cocina Española de Juan Altamiras - Riley, Gillian (Petits Propos Culinaires, 2018)
Vicky Hayward: New Art of Cookery, a Spanish friar’s kitchen notebook by Juan Altamiras, Rowman & Littlefield, 2017: 294pp., hardback, £24.95 Vicky Hayward: Nuevo Arte de la Cocina Española de Juan Altamiras, traducción de Cristina Macía, Ariel, 2017: 494pp., hardback, £32.35